Tracheal extubation under Narcotrend EEG monitoring at different depths of anesthesia after tonsillectomy in children: a prospective randomized controlled study - An, Hongqiang; Zhang, Xifeng; Chen, Lingling (Frontiers in Pediatrics, 2024)
Objective This study aims to investigate whether tracheal extubation at different depths of anesthesia using Narcotrend EEG (NT value) can influence the recovery quality from anesthesia and cognitive function of children who underwent tonsillotomy. Methods The study enrolled 152 children who underwent tonsillotomy and were anesthetized with endotracheal intubation in our hospital from September 2019 to March 2022. These patients were divided into Group A (conscious group, NT range of 95–100), Group B (light sedation group, NT range of 80–94), and Group C (conventional sedation group, NT range of 65–79). A neonatal pain assessment tool, namely, face, legs, activity, cry, and consolability (FLACC), was used to compare the pain scores of the three groups as the primary end point. The Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA) scales were used to evaluate the cognitive function of children in the three groups before and after surgery as the secondary end points. Results Differences were observed in the awakening time and FLACC scores after awakening among the three groups (P < 0.05). Among them, Group A exhibited a significantly shorter awakening time and higher FLACC score after awakening than those in Groups B and C (both P < 0.05). The total incidence of adverse reactions in Group B was significantly lower than that in Groups A and C (P < 0.05). No significant difference was observed in MMSE and MoCA scores before the operation and at 7 days after the operation among the three groups (P > 0.05), but a significant difference was found in MMSE and MoCA scores at 1 day and 3 days after the operation among the three groups (P < 0.05). In addition, MMSE and MoCA scores of the three groups decreased significantly at 1 day and 3 days after the operation than those at 1 day before the operation (P < 0.05). Conclusion When the NT value of tonsillectomy is between 80 and 94, tracheal catheter removal can effectively improve the recovery quality and postoperative cognitive dysfunction of children.